Endogenous mucosal phosphatases characterization in duodenum brush border membrane of laying hens - Hanauska, Anna; Sommerfeld, Vera; Schollenberger, Margit; Huber, Korinna; Rodehutscord, Markus (Frontiers in Physiology, 2025)
Chicken mucosal phosphatases can partially degrade phytate contained in the feed. Little is known about the characteristics and degradation products of such mucosal phosphatases and the effects of age and genetic strain of the chicken. The objective of this study was to characterize endogenous mucosal phosphatases of two laying hen strains fed diets with or without mineral phosphorus (P) before and after the onset of egg laying. Hens of the strains Lohmann Brown-classic (LB) and Lohmann LSL-classic (LSL) were sacrificed in weeks 19 and 24 of age after 4 weeks of feeding one of two diets with (P+) or without (P-) mineral P supplement. Mucosa of the duodenum was collected, and the brush border membrane (BBM) of enterocytes was enriched and used for phosphatase activity determination. Additionally, the BBM was used in a modified three-step in vitro assay to study the InsP6 degradation products. The results of both in vitro assays were not significantly affected by hen strain and diet. The activity of mucosal phosphatase in 19-week-old hens was, on average, 0.8 µmol Pi/g BBM protein/min lower than in 24-week-old hens (P < 0.002). Consistently, the InsP6 concentration in the incubation residue was significantly higher in 19-week-old hens than in 24-week-old hens (P < 0.001). In the incubation residue, the concentrations of Ins(1,2,3,4,5)P5, Ins(1,2,3,4,6)P5, and Ins(1,2,3,4)P4 were significantly lower (P ≤ 0.002), and those of InsP3 and InsP2 were significantly higher (P ≤ 0.027) when BBM of 24-week-old hens was used compared to 19-week-old hens. The InsP6 degradation products suggest the activity primarily of a 6- and secondarily of a 5-phytase in the duodenal mucosa. The consistent results from both in vitro assays provide a comprehensive characterization of these enzymes. Under the conditions of this study, small intestine calcium concentration appeared to influence mucosal enzyme activity more than dietary mineral P supplementation.